2021
DOI: 10.3390/v13112228
|View full text |Cite
|
Sign up to set email alerts
|

Curing Cats with Feline Infectious Peritonitis with an Oral Multi-Component Drug Containing GS-441524

Abstract: Feline infectious peritonitis (FIP) caused by feline coronavirus (FCoV) is a common dis-ease in cats, fatal if untreated, and no effective treatment is currently legally available. The aim of this study was to evaluate efficacy and toxicity of the multi-component drug Xraphconn® in vitro and as oral treatment in cats with spontaneous FIP by examining survival rate, development of clinical and laboratory parameters, viral loads, anti-FCoV antibodies, and adverse effects. Mass spectrometry and nuclear magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
135
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(142 citation statements)
references
References 77 publications
4
135
1
2
Order By: Relevance
“…This study also showed that the concentration of active ingredient MT0901 in Mutian X tablets can be specified only by the package insert, and additionally mentioned a concern about no approved information on its purity, accuracy, or lot-tolot variation, because of its position as a veterinary drug unauthorized by a regulatory agency. However, all 18 cats were apparently cured with no critical adverse events detected, supporting that the dose given in the package insert was approximately correct [23]. Thus, the therapeutic efficacy of Mutian X against naturally occurring FIP in 18 pet cats were assessed in this study for the first time.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This study also showed that the concentration of active ingredient MT0901 in Mutian X tablets can be specified only by the package insert, and additionally mentioned a concern about no approved information on its purity, accuracy, or lot-tolot variation, because of its position as a veterinary drug unauthorized by a regulatory agency. However, all 18 cats were apparently cured with no critical adverse events detected, supporting that the dose given in the package insert was approximately correct [23]. Thus, the therapeutic efficacy of Mutian X against naturally occurring FIP in 18 pet cats were assessed in this study for the first time.…”
Section: Discussionmentioning
confidence: 59%
“…Mutian X, a drug product that can be administered orally, has been reported to be markedly effective against spontaneously occurring FIP [22]. Recently, a significant effect of oral administration of Mutian X has been shown on 18 cats with naturally occurring FIP, resulting in recovery with dramatic improvement of clinical and laboratory parameters at the early phase of treatment and no serious adverse effects, and the chemical structure of the active ingredient of Mutian X was identified as that of GS-441524 by means of chemical and structural analysis [23]. This study also showed that the concentration of active ingredient MT0901 in Mutian X tablets can be specified only by the package insert, and additionally mentioned a concern about no approved information on its purity, accuracy, or lot-tolot variation, because of its position as a veterinary drug unauthorized by a regulatory agency.…”
Section: Discussionmentioning
confidence: 99%
“…The clinicopathological findings of systemic disease including the fever and diagnostic imaging findings resolved in this case after treatment with the antiviral injections suspected to be the nucleoside analogue GS441524. A recent study demonstrated high efficacy of an unregistered oral multi‐component drug containing GS441524 in curing naturally‐occurring FIP (Krentz et al., 2021). However, the clinical presentation described in the cat in this report could have been caused by other infections (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, a different direct-acting antiviral (DAA) (remdesivir), a nucleoside analog that acts as a chain terminator and with less toxicity concerns compared to ribavirin, rapidly rose to prominence in treating hospitalized COVID-19 patients, being used in an injectable form. Despite initial enthusiasm, remdesivir has not proven to be effective in such patients in robust clinical trials; however, several reports have demonstrated the clinical benefit of the related nucleoside analog GS-441524 in treating cats with FIP, including effusive, noneffusive, and neurologic forms of the disease [ 194 , 195 , 196 , 197 ]. At the time of writing, investigations into the efficacy of remdesivir in treating FIP are being conducted in Australia and the United Kingdom.…”
Section: Clinical Care and Therapeutic Optionsmentioning
confidence: 99%